EMPATHY AND SYMPATHY AND SOCIAL DEVELOPMENT IN ADOLESCENTS - Burteshova A.B. (European Science Publishing, 2024)
The article is devoted to the problem of empathy of modern teenagers. Primary diagnostics of the level of empathy in the subjects showed that there is a part of adolescents in whom the ability to empathize is weakly expressed. Adolescents may have difficulty interacting with other people, in building close relationships. Experimental and control groups were formed, which included students with a low level of empathy in terms of the general indicator. The formation of empathy in younger adolescents was carried out in the course of the implementation of a specially designed program of developing activities.The results of statistical data processing procedures before and after the training program showed that there is a significant positive dynamics of empathy indicators in adolescents. It is shown that a specially designed program of classes aimed at the formation of empathy components helps to overcome the difficulties of adolescents in reflecting and understanding feelings, establishing trusting relationships in communication with peers
Keywords: empathy, development of empathy of adolescents, conditions for the formation of empathy.